Assessment of residual ultimate strength on plate girders with web opening under compression-bending loadings. (1st September 2019) - Shen, Wei; Zhao, Yingjiang; Li, Lun; Qiu, Yu; Liu, Enqian
Abstract: Plate girders with web opening are commonly applied in marine structures for the demands of outfitting and light-weight. The presence of perforations will cause the structural discontinuity, stress concentration and declining of ultimate bearing capacity. In addition to the bending loading, the deck strong beam is often subjected to transverse loading, which belongs to the typical compression-bending biaxial loadings. In this paper, the ultimate strengths of the perforated girders under compressive-bending loadings was investigated by experimental analysis and nonlinear finite element analysis. Meanwhile, the effect of welding-induced initial deflections, such as the shape of initial deflection and the magnitude of initial deflection, on the collapse behavior of plate girders with web opening was investigated thoroughly, by using numerical method in which the welding-induced initial imperfections are simulated properly. It is concluded that the initial imperfections and longitudinal load have important influences on the residual ultimate strength of perforated girder. Highlights: The ultimate strengths of perforated girders under compressive-bending loadings was investigated by experimental analysis. Nonlinear finite element calculation are used to verify the experimental results. The effect of welding-induced initial deflections on the collapse behavior of perforated girders was investigated thoroughly.